Self-Focused Attention, Meaning, and Posttraumatic Growth: The Mediating Role of Positive and Negative Affect for Bereaved Women. - Boyraz, Güler; Efstathiou, Natalie (Journal of Loss & Trauma)
This study examined the mediating impact of positive and negative affect on the relationship between two distinct self-focusing tendencies (i.e., reflection and rumination) and meaning and posttraumatic growth among bereaved women. Supporting the study hypotheses, positive affect mediated the relationship between self-focusing tendencies and both meaning and posttraumatic growth. Reflection and rumination also had indirect effects on meaning through negative affect. The study model accounted for 25% of the variance in positive affect, 31% of the variance in negative affect, 43% of the variance in PTG, and 58% of the variance in meaning. These findings underlined the importance of intellectual self-reflection and positive affect in fostering personal growth and adjustment of bereaved women. Results and implications of the findings are discussed in the light of existing literature on bereavement and self-focusing tendencies.